RELIGIOUS MODERATION LEVELS AMONG THE STUDENTS OF ISLAMIC EDUCATION DEPARTMENT IN THE FACULTY OF EDUCATION AND TEACHER TRAINING AT UIN MATARAM - Andrian, Paris; Erwin Padli (Tahiro : Journal of Peace and Religious Mederation, 2024)
The issue of intolerance on campus is a compelling subject for study today, particularly within the Islamic Religious Education (Pendidikan Agama Islam: PAI) programmes under the Ministry of Religion, which should exemplify a positive attitude towards religious moderation. This research aims to examine the level of religious moderation among Islamic students of the Religious Education programme. In particular, the study describes the level of religious moderation of 2021 batch students of the Islamic Religious Education programme at the Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri (UIN) Mataram. To assess the level of religious moderation among the students, the researchers used a descriptive qualitative research method. Data were collected through interviews, observation and documentation. The research findings indicate that religious moderation is an attitude and effort to establish religion as a principle for avoiding extreme positions and consistently seeking middle ground in uniting society. The level of religious moderation among the students of the 2021 batch (sixth semester) of the Islamic Religious Education programme can be classified as high, as evidenced by their effective implementation of the religious moderation indicators. These indicators consist of four elements: national commitment, tolerance, anti-violence stance, and accommodation of local culture.